Bangladesh textile and garments industry, manufacturing market-growth, trends and forecasts in reference with chargeurs PCC (Fashion technologies) - Javed, Syed Imtyaz (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.